1984
DOI: 10.9753/icce.v19.40
|View full text |Cite
|
Sign up to set email alerts
|

Run-Up of Random Waves on Gentle Slopes

Abstract: This paper investigates the following characteristics of run-up of random waves on gentle slopes experimentally: (1) the run-up wave energy spectrum, (2) the ratio of the number of run-up waves to that of incident waves, (3) the relationship between the representative run-up height, the deep-water wave steepness and the beach slope, (4) the run length of run-up heights, and (5) the effect of wave grouping on representative run-up heights. Main results are summarized in the chapter of conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The gradient of power density function in the saturated range at the high frequency side of the peak follows -3 power of the frequency (f~3) at the outside of the breaker zone(Sawaragi and Iwata, 1980) and follows -4 power of frequency (f~4) inside the surf zone, as reported by Mizuguchi(1984), and Mase and Iwagaki(1984).…”
Section: Raw Datasupporting
confidence: 63%
“…The gradient of power density function in the saturated range at the high frequency side of the peak follows -3 power of the frequency (f~3) at the outside of the breaker zone(Sawaragi and Iwata, 1980) and follows -4 power of frequency (f~4) inside the surf zone, as reported by Mizuguchi(1984), and Mase and Iwagaki(1984).…”
Section: Raw Datasupporting
confidence: 63%
“…This agreement lends credibility to the basic model formulation and derived solution, although in order to obtain a model that can be used for reliable estimates of dune erosion R and C s must be accurately predicted. Initially, several different runup height formulas were tested to predict R (e.g., Hunt, 1959;Mase and Iwagaki, 1984;Holman, 1986;Larson and Kraus, 1989a;Mayer and Kriebel, 1994), but the resulting optimum values on C s displayed a large variation between the individual cases making application of the model difficult.…”
Section: Large Wave Tank Datamentioning
confidence: 99%
“…Mase and Iwagaki (1984) ran a series of tests in the laboratory with random waves and found that the ratio of the number of individual run-up waves to that of incident waves decreased as the beach slope decreased. Based on additional laboratory experiments, Mase (1989) developed an empirical formula to predict the maximum run-up on a range of slopes while accounting for swash interaction between random waves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The catch-up and absorption mechanism of swash interaction was explicitly modeled by Mase and Iwagaki (1984) employing empirical data and Mase (1988) and Baldock and Holmes (1999) by superimposing run-up parabolas using the ballistic model without friction. Mase and Iwagaki (1984) ran a series of tests in the laboratory with random waves and found that the ratio of the number of individual run-up waves to that of incident waves decreased as the beach slope decreased.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation